Privatisation of Prisons and Prison Services in South Africa - Ntsobi, Mfanelo, Patrick (My University, 2022)
This study explored options for the provision of efficient prison services in South Africa. The researcher compared public and private prisons with respect to costs, quality, accountability and impact on jobs. The study also drew lessons from the international experience on prison privatisation. The primary objective of the study was to develop practical options for privatisation of prison and prison services in South Africa. The study includes a literature review as well as an assessment and selection of theoretical frameworks. The researcher relied on reports and legislation(s) with respect to prison privatisation. A case study was developed on three countries where prison privatisation had gained momentum (USA, Australia and UK). In Africa, at the research report focused on Lesotho, Malawi and Botswana, focusing on the extent of overcrowding and prison privatisation in these respective countries. The study found that, the legislation regulating private prisons favours private contractors and needs to be revisited. It also emerged that the privatisation of prisons and prison services has become an international trend, spreading to other continents such as Africa, Asia and South America. The study also found that the project on private prisons was rushed and not properly piloted in South Africa, however, it also came out that private prisons could coexist alongside private prisons. The general claim that private prisons are cheaper than public prisons could not be proved, especially in relation to South Africa. The main finding in relation to costs was that, private prisons have at least helped to come up with a formula to establish how much it really costs to keep a person in prison. Finally, the study concluded that the topic on prison privatisation needs further exploration and that; there is a need for renewed partnerships between private and public prisons that would be mutually beneficial.
Keywords: Efficiency; New public management; Overcrowding; Prison Industrial Complex; Prison privatisation; Public Private Partnerships (PPP)